Changes in the circRNA expression profile of PC12 cells induced by TDCIPP exposure may regulate the downstream NF-κB pathway via the Traf2 gene. (September 2020) - Li, Zhenxin; Sun, Jingran; Liu, Weili; Wu, Jin; Peng, Hui; Zhao, Youquan; Qiao, Haixuan; Fang, Yanjun
Abstract: As a commonly used organophosphorus flame retardant (OPFR), tris (1, 3-dichloro-2-propyl) phosphate (TDCIPP) has become an environmental pollutant. Studies have shown that TDCIPP exposure has many toxic effects, such as neurotoxicity, reproductive development toxicity and endocrine disturbance. CircRNAs are circular noncoding RNAs that have been found to play important roles in the occurrence of a variety of diseases. However, it is unclear whether circRNAs play a role in the cytotoxicity induced by TDCIPP exposure. In this study, we analysed the circRNA microarray results of a control group and a TDCIPP exposure group of PC12 cells and detected 3432 differentially expressed circRNAs (P < 0.05), of which 1682 were upregulated and 1750 were downregulated in the TDCIPP-exposure group. The expression levels of 2 upregulated and 3 downregulated circRNAs were verified by real-time quantitative PCR, and the results were consistent with the microarray results. Then, ceRNA analysis was performed on several kinds of circRNAs to predict the possible binding miRNAs and binding sites. The target genes were analysed by Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway analysis. Through predictive analysis, it was found that rno_circRNA_013845, rno-miR-361-3p, and rno-miR-702-3p may be involved in the regulation of Traf2 expression, thereby affecting the expression of the downstream NF-κB signalling pathway and causing apoptosis. Highlights: 1.TDCIPP exposure cause apoptosis and affects circRNA expression in PC12 cells. 2.Microarray analysis reveal rno_circRNA_013845 and rno_circRNA_017350 can be combined with Traf2 mRNA. 3.CeRNA network improves Traf2 expression and its downstream NF-κB signalling pathway.